Effect of nickel precursor and catalyst activation temperature on methanation performance - Buyan-Ulzii, Battulga; Daariimaa, Odbayar; Munkhdelger, Chuluunsukh; Oyunbileg, Galindev; Enkhsaruul, Byambajav (Mongolian Journal of Chemistry, 2018)
This work studied an effect of anionic precursor on the preparation of active and fine nickel metal catalysts for syngas methanation. Nickel catalysts were pr¬epared by impregnation-co-precipitation method. Nickel hydrate salts of Ni(NO3)2·6H2O, NiSO4·6H2O and NiCl2·6H2O were used as a metal catalyst precursor, and the obtained catalysts were named as Ni/Al (N), Ni/Al (S) and Ni/Al (Cl), respectively. Methanation synthesis of carbon monoxide was carried out in a fixed bed stainless reactor. Prior to experiment, the catalyst powder was pressed into tablets, then crushed and sieved to use 0.5-0.9 mm particles. Reactions were performed at the temperature of 350 °C in the pressure of 3 atm of H2:CO syngas (the molar ratio of 3:1) with the GHSV of 3000 h-1. In the present methanation conditions, the Ni/Al (N), Ni/Al (S) and Ni/Al (Cl) catalysts gave the CH4 selectivity of 93%, 18% and 91% (vol.), respectively. The XRD and ICP-OES analysis clarified that although the Ni/Al (S) catalyst contained a similar nickel amount of 17.4 wt % to other two catalysts, its metal distribution was poor. Also the low activity of the Ni/Al (S) catalyst was caused by the contamination of remained sulfur from sulfate precursor. This work also examined an influence of catalyst activation temperature pre-synthesis. The Ni/Al (N) catalyst was reduced by pure hydrogen gas at different temperatures of 350 ºС, 400 ºС or 450 ºС. The catalyst activated at 400 ºС produced the highest CH4 amount of 0.087 mmol·g-1cat for the duration of 1h methanation. An initial temperature of methane formation was the lowest for the Ni/Al (N) catalyst which was activated at 400 ºС among three catalysts.